Land ecological security assessment for Yancheng city based on catastrophe theory - Wang Liang; Bian Zhengfu; Chen Hongquan (Earth Sciences Research Journal)
Based on actual land use in Yancheng city, this paper establishes the ecological security of the land index system from the perspectives of economy, society and ecological environment. Using the catastrophe theory and pressure-state-response (PSR) model, the purpose of the research was to judge the degree of land ecological security in Yancheng city from 2002 to 2011 and determine the requirements to ensure the sustainable development of this region. The results showed that over the ten years, the pressure, state, response and synthetic values of the land ecological security were evaluated as safe in 2003 and 2007 and at middle level in 2002 and for 2004 to 2006 and then dropped to insecure for 2008 to 2009 and very insecure for 2011 to 2012. The ecological security level and circumstance of land use in Yancheng city has generally declined. During this period, the land use pattern of Yancheng city was under tremendous pressure from the conflict between rapid urbanization and economic development, as well as conservation and rehabilitation of the eco-environment. This research shows that conditions for the land ecosystems of Yancheng city are not optimistic and, as such, should draw the attention of responsible government departments. Future policy options should aim to mitigate these problems through the control of population growth and the improvement in quality of life, protection of wetland and forest land, application of scientific concepts of development, coordination of economic development and land utility, and strengthening the control functions of land-use planning.